The prevalence of human papillomavirus infections and associated risk factors in men-who-have-sex-with-men in Cape Town, South Africa. Issue 1 (December 2016) - Müller, Etienne; Rebe, Kevin; Chirwa, Tobias; Struthers, Helen; McIntyre, James; Lewis, David
Abstract Background We investigated the prevalence of human papillomavirus (HPV) infection and associated behavioural risk factors in men-who-have-sex-with-men (MSM) attending a clinical service in Cape Town, South Africa. Methods MSM were enrolled at the Ivan Toms Centre for Men's Health in Cape Town. A psychosocial and sexual behavioral risk questionnaire was completed for each participant and urine, oro-pharyngeal and anal swabs were collected for HPV testing using the Linear Array HPV Genotyping Test. Logistic regression analyses were performed to determine sexual risk factors associated with HPV infection at the three anatomical sites. Results The median age of all 200 participants was 32 years (IQR 26-39.5), of which 31.0 % were black, 31.5 % mixed race/coloured and 35.5 % white. The majority of the participants (73.0 %) had completed high school, 42.0 % had a tertiary level qualification and 69.0 % were employed. HPV genotypes were detected in 72.8 % [95 % CI: 65.9–79.0 %], 11.5 % [95 % CI: 7.4–16.8 %] and 15.3 % [95 % CI: 10.5–21.2 %] of anal, oro-pharyngeal and urine specimens, respectively. Prevalence of high-risk (HR)-HPV types was 57.6 % [95 % CI: 50.3–64.7 %] in anal samples, 7.5 % [95 % CI: 4.3–12.1 %] in oro-pharyngeal samples and 7.9 % [95 % CI: 4.5–12.7 %] in urine, with HPV-16 being the most common HR-HPV type detected at all sites. HPV-6/11/16/18 was detected in 40.3 % [95 % CI: 33.3–47.6 %], 4.5 % [95 % CI: 2.1–8.4 %] and 3.2 % [95 % CI: 1.2–6.8 %] of anal, oro-pharyngeal and urine samples, respectively. Multiple HPV types were more common in the anal canal of MSM while single HPV types constituted the majority of HPV infections in the oropharynx and urine. Among the 88 MSM (44.0 %) that were HIV positive, 91.8 % [95 % CI: 83.8–96.6 %] had an anal HPV infection, 81.2 % [95 % CI: 71.2–88.8 %] had anal HR-HPV and 85.9 % [95 % CI: 76.6–92.5 %] had multiple anal HPV types. Having sex with men only, engaging in group sex in lifetime, living with HIV and practising receptive anal intercourse were the only factors independently associated with having any anal HPV infection. Conclusions Anal HPV infections were common among MSM in Cape Town with the highest HPV burden among HIV co-infected MSM, men who have sex with men only and those that practiced receptive anal intercourse. Behavioural intervention strategies and the possible roll-out of HPV vaccines among all boys are urgently needed to address the high prevalence of HPV and HIV co-infections among MSM in South Africa.